2021
DOI: 10.1111/oik.08276
|View full text |Cite
|
Sign up to set email alerts
|

The influence of provisioning on animal‐mediated seed dispersal

Abstract: Anthropogenic provisioning of food to wildlife is ubiquitous across the globe. It may be intentional such as in the form of bird feeders or offering of food to animals by tourists, or unintentional when animals use anthropogenic food sources like crops, plantations or garbage dumps. Provisioning has profound effects on wildlife ecology and behaviour, but the consequences of these changes to mutualistic and antagonistic interactions have rarely been investigated. Here we demonstrate how provisioning can affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…The impact of wildlife provisioning on the environment is often overlooked in provisioning studies, with experimental outcomes frequently focused on only individuals or target species. However, some evidence suggests that provisioning can be detrimental to ecosystems by altering natural food webs [37], changing ecosystem processes such as seed dispersal [38], and encouraging the proliferation of non-native species [39]. Alternatively, under conservation settings such as following a catastrophic bushfire, provisioning might assist in sustaining natural wildlife populations or reducing habitat damage and protecting valuable natural areas (e.g., by reducing grazing pressure on regenerating areas).…”
Section: One Welfarementioning
confidence: 99%
“…The impact of wildlife provisioning on the environment is often overlooked in provisioning studies, with experimental outcomes frequently focused on only individuals or target species. However, some evidence suggests that provisioning can be detrimental to ecosystems by altering natural food webs [37], changing ecosystem processes such as seed dispersal [38], and encouraging the proliferation of non-native species [39]. Alternatively, under conservation settings such as following a catastrophic bushfire, provisioning might assist in sustaining natural wildlife populations or reducing habitat damage and protecting valuable natural areas (e.g., by reducing grazing pressure on regenerating areas).…”
Section: One Welfarementioning
confidence: 99%
“…The simplified microbial communities that characterise disturbed systems diminish their resilience, increasing sensitivity to additional disturbance events. The idea of using visiting animals to fast‐track restoration has been trialled before (Sengupta et al, 2022), primarily in reforesting agricultural land where the addition of artificial perches to cleared areas facilitates dispersal of large‐seeded plants by visiting birds (Athiê & Dias, 2016; Wunderle, 1997), which can be expanded to smaller‐seeded groups via the related concept of induced seed dispersal (Silva et al, 2020) or scaled up by integrating revegetation of small patches of trees to facilitate colonisation of animal‐dispersed trees (applied nucleation; Zahawi et al, 2013). Although more relevant in terrestrial systems, the potential for wide‐ranging aquatic organisms to seed microbial recovery has been noted by researchers working on both marine reefs (e.g.…”
Section: Approach Applications and Benefits Limitations Referencesmentioning
confidence: 99%
“…Events that cause an overabundance of a preferred resource (e.g., masting, human subsidies or biological invasions) could, therefore, lead to a cryptic function loss of seed dispersal by subordinates (McConkey & O’Farrill, 2015; Box 2). It is generally appreciated that provisioning of anthropogenic resources can lead to declines in seed dispersal by reducing fruit removal rates by wildlife (Sengupta et al, 2021), but there is limited understanding of how changes in social behaviour due to provisioning may be a mechanism by which seed dispersal is affected by anthropogenic resources. It has been shown that animal social network structure is relaxed near anthropogenic habitats (Belton et al, 2018; Morrow et al, 2019), indicating that a potential mechanism by which anthropogenic resources may reduce seed‐dispersal services is when high‐quality foods are no longer defended by dominant individuals.…”
Section: Consequences Of Global Change For Socially Mediated Seed Dis...mentioning
confidence: 99%